2019
DOI: 10.1002/ece3.5556
|View full text |Cite
|
Sign up to set email alerts
|

Matching population diversity of rhizobial nodA and legume NFR5 genes in plant–microbe symbiosis

Abstract: We hypothesized that population diversities of partners in nitrogen‐fixing rhizobium–legume symbiosis can be matched for “interplaying” genes. We tested this hypothesis using data on nucleotide polymorphism of symbiotic genes encoding two components of the plant–bacteria signaling system: (a) the rhizobial nodA acyltransferase involved in the fatty acid tail decoration of the Nod factor (signaling molecule); (b) the plant NFR5 receptor required for Nod factor binding. We collected three wild‐growing legume spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Rhizobiales (Alpha subclass of the Proteobacteria) was the core taxon in IP, and Burkholderiales (Delta subclass of the Proteobacteria) is the core taxon in IS ( Figure 7A ). The observed results corroborated those of a previous study, which showed population diversities of partners in N−fixing rhizobium-legume symbiosis to be matched ( Igolkina et al, 2019 ). These results indicated that even in the same microorganism library, plants can still actively recruit plant-associated microorganisms from the soil to construct specific microbial communities.…”
Section: Discussionsupporting
confidence: 91%
“…Rhizobiales (Alpha subclass of the Proteobacteria) was the core taxon in IP, and Burkholderiales (Delta subclass of the Proteobacteria) is the core taxon in IS ( Figure 7A ). The observed results corroborated those of a previous study, which showed population diversities of partners in N−fixing rhizobium-legume symbiosis to be matched ( Igolkina et al, 2019 ). These results indicated that even in the same microorganism library, plants can still actively recruit plant-associated microorganisms from the soil to construct specific microbial communities.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, any structural variability in the NF tail (i.e., chain length or double bond positions) can potentially have an impact on NF-dimer specificity. This conclusion is in line with previous results, where the correspondence between population diversities of the rhizobial nodA gene (coding for the acyltransferase involved in the fatty acid tail decoration of the NF) and plant heterodimeric receptor genes was demonstrated (Igolkina et al, 2019). Plausible mechanisms of this linkage, namely coordinated variability of amino acids in contact with the surface of the receptor dimer adjacent to the NF fatty tail, were proposed (Igolkina et al, 2018).…”
Section: Protein-ligand Dockingsupporting
confidence: 91%
“…Previous studies have implicated PPIs in plant–microbe interactions. For example, membrane‐bound receptor flagellin‐sensing 2 detects and binds bacterial flagellin (flg22) to trigger PAMP‐triggered immunity and confer resistance to bacteria (Sun et al, 2013); and the legume NFR5 receptor can recognize rhizobial nodA acyltransferase to regulate the Nod‐factor signaling pathway (Igolkina et al, 2019). Thus, the construction of plant–microbe interaction networks can contribute to the understanding of interspecies interactions and elucidate the cross‐linking mechanism among different species from another perspective.…”
Section: Discussionmentioning
confidence: 99%